The The Use of Generative AI to Improve Reading Literacy Skills among Generation Alpha Students: A Systematic Literature Review - Fitri Andini dini; Nadila Putri Nassel; Afifah Rahmadani; Nur Syakila Mulya; Rina Nurul Aisyah; Hanifa Dzakiyya; Putri Hana Pebriana (The Future of Education Journal, 2026)
As the mid-2020s unfold, the integration of Generative Artificial Intelligence (GenAI) has transformed the reading literacy paradigm for Generation Alpha from the consumption of static texts to engagement with dynamic text-based interactions. This study aims to examine the role of GenAI as a cognitive partner in enhancing reading literacy through a Systematic Literature Review (SLR) of scholarly studies and policy documents published between 2021 and 2026. Employing a qualitative descriptive-analytical approach, the study synthesizes data from relevant national and international journal publications. The findings indicate that the use of technologies such as AI-powered reading assistants and interactive storytelling significantly improves elementary school students’ reading fluency, comprehension, and active engagement. However, the review also identifies several critical challenges, including the risk of AI hallucinations, the potential decline of cognitive skills due to excessive technological dependence, and the widening AI divide. The study concludes that the effectiveness of GenAI in education largely depends on teachers’ digital literacy and the development of an AI Literacy Framework that emphasizes metacognitive awareness and ethical competencies. Furthermore, inclusive policies are required to ensure that this literacy transformation can be accessed equitably by all segments of Generation Alpha.